Green tax reform, endogenous innovation and the growth dividend - Christos Karydas; Lin Zhang (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
We study theoretically and numerically the effects of an environmental tax reform using endogenous growth theory. In the theoretical part, mobile labor between manufacturing and R&D activities, and elasticity of substitution between labor and energy in manufacturing lower than unity allow for a growth dividend, even if we consider preexisting tax distortions. The scope for innovation is reduced when we consider direct financial investment in the lab, or elastic labor supply. We then apply the core theoretical model to a real growing economy and find that a boost in economic growth following such a carbon policy is a possible outcome. Lump-sum redistribution performs best in terms of effciency measured by aggregate welfare, while in terms of equity among social segments its progressive character fails when we consider very high emissions reduction targets.
Keywords: C63; E62; O44; Q43; Q48; 330; Climate Policy; Green Tax Reform; Induced Innovation; Endogenous Growth; Numerical Modelling; Ökosteuer; Steuerreform; Innovation; Klimapolitik; Endogenes Wachstumsmodell